REVIEW ON WOUND HEALING THERAPEUTIC REGIMENS IN AYURVEDA (International Journal of Ayurveda and Pharma Research, 2020)
Wound healing is type of tissue repair involving number of processes. These processes influenced by both systemic factors and local factors. Nutrition, metabolic status, circulatory status, hormone levels are the main systemic factors which influence wound healing. In addition to these, infection, mechanical factors, foreign bodies, size, location and type of wound are also influence the wound healing process. Various kinds of complications are occurred when wound is not properly healed. In Ayurveda, the term Vrana is equated to wound of modern parlance and the drugs having both Vranashodhana (wound cleansing) and Vranaropana (wound healing) properties play an important role in wound management. Considering this, single and compound formulations having Vranashodhana and Vranaropana properties are compiled from classical texts and compendia. Clinical trials on wound management through are Ayurvedic drugs/regimen reviewed and presented.